PENGEMBANGAN INSTRUMEN PENILAIAN THREE-TIER MULTIPLE CHOICE UNTUK MENGUKUR KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI TERMOKIMIA - Rina Elvia; Elvinawati; Putri Nopita Sari (University of Bengkulu, 2024)
The purpose of this study is to develop a three-level multiple choice assessment instrument to measure critical thinking skills of students at SMA Negeri 5 Bengkulu City on thermochemical material. The development model used is the ADDIE model. The research subject is class XI MIPA 4 at SMA Negeri 5 Bengkulu City in the academic year 2022/2023. The research data were obtained from needs analysis, expert validation sheets, empirical test analysis, reliability, difficulty level, discriminatory power, distractor analysis, and analysis of students' critical thinking skills. The number of instruments developed is 20 three-tier multiple choice questions. The results of the study: (1) The three-level multiple choice test instrument on the thermochemical material developed was declared valid by the validator with a minimum CVR value of 0.78 and a CVI value of 0.91 with a very good category (2) The results of the empirical validity test carried out on 68 students and obtained 14 valid questions (3) A three-level assessment instrument with several choices that can be used to measure students' thinking skills (4) The results of the implementation of developing critical thinking skills instruments obtained 2 students with very critical categories, 2 students with critical categories, 16 students in the moderately critical category, 13 students in the less critical category, and 1 student in the uncritical category. (4) The results of the development of the three-tier multiple choice assessment instrument can be used to measure students' critical thinking skills.